A Reasonable Estimate of the Return on Human Capital Investment for Migrant Workers in China - Lei SUN, Zhuojing FU (Forest Chemicals Review, 1970)
There are structural differences in the returns on human capital investment between migrant workers and urban domiciled labor in China, there because of the urban-rural segmentation of the labor market and extremely high mobility costs. These structural differences vary by marital status, age structure, and migration range, leading to the potential bias of using the traditional Mincer wage equation to estimate returns on human capital investment for migrant workers. An empirical study based on CFPS data supports the theory. This study enables a more reasonable understanding and estimation of the returns on human capital investment of Chinese migrant workers.